Tertiary treatment of palm oil mill effluent (POME) using hydrogen peroxide photolysis method - Abdullah, Shakila (2008)
Palm oil mill effluent (POME) is in the form of highly concentrated dark brown colloidal suspension. Despite of being treated using biological treatment, the wastewater is still coloured and indicates the remaining of significant concentrations of organics in the effluent discharge. Hence, tertiary treatment is required to further improve the quality of the effluent. Hydrogen peroxide photolysis (UVIH202) is one of the advanced oxidation process (AOP) that can be an option to treat the biologically treated POME (BT-POME). Experiments were conducted to investigate the removal of colour and COD in order to assess the effectiveness and feasibility of (UVIH20 2) catalytic system for tertiary treatment of POME. The operating parameters such as hydrogen peroxide dosage, pH value and initial BT-POME concentrations were evaluated. The removal process could be fitted by the zeroth orger for COD and second order kinetics for colour. The efficiency of colour and COD removal ranged from 7.3%-61.3% and 7.4%-61.1% respectively. Examination of the effect showed the maximum removal could be achieved under optimal conditions of H202 dosage of 250 mgIL and pH of 7.5. In general, the three factors mentioned earlier affect the performance of the process and discussed in the report. Further study is needed to improve the performance of UVIH202 process in treating BT-POME.